Analisis Penurunan Produksi Air Tawar pada Fresh Water Generator di MV Sky Free - Muhammad Miftahul Alim; Maxima Ari Saktiono; Daryanto Daryanto (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
This study examines the decline in the performance of the Fresh Water Generator (FWG), an auxiliary system used to produce fresh water for operational activities and crew consumption aboard MV Sky Free. The FWG experienced a reduction in production capacity from the normal output of 10–12 tons/day to only 6–8 tons/day, creating the potential for freshwater shortages during vessel operations. The research employed a descriptive quantitative approach, with data collected through direct observation, documentation, and questionnaires distributed to relevant personnel. Data were analyzed using the Failure Mode and Effect Analysis (FMEA) method to determine the priority of failures based on their Risk Priority Number (RPN). The analysis revealed that scale accumulation on the evaporator plates represented the most critical failure mode, with an RPN of 216, followed by localized overheating of the heating pipe (192), leakage in the vacuum system (135), and condenser fouling combined with non-condensable gas accumulation (120). These failures reduce heat transfer efficiency, disrupt evaporation and condensation processes, and ultimately lower freshwater production. Corrective measures include cleaning the evaporator and condenser, repairing vacuum system leaks, and conducting comprehensive component inspections. Preventive actions involve implementing scheduled maintenance, monitoring operational parameters, and performing regular inspections. Consistent application of preventive and corrective maintenance successfully restores FWG performance, enabling freshwater production to return to its normal capacity of 10–12 tons/day and ensuring a sustainable freshwater supply for ship operations.